Turning a new leaf: Social and land use drivers of urban tree canopy change in the Chicago Metropolitan Area 2010–2017 - Jackson D. Lyall; Lindsay E. Darling; Dexter H. Locke; Brady S. Hardiman (Urban Forestry & Urban Greening, 2025)

Molecular characterization of a polymycovirus in Leptosphaeria biglobosa - Nesma M. Samir; Jacob Locke-Gotel; Syun-Ichi Urayama; Adel A. El-Morsi; Ghada A. El-Sherbeny; Yongju Huang; Bruce D. L. Fitt; Hiromitsu Moriyama; Robert H. A. Coutts; Ioly Kotta-Loizou (Archives of Virology, 2025)
Leptosphaeria biglobosa is a phytopathogenic ascomycete of Brassica napus that causes phoma stem canker/blackleg. A new double-stranded RNA (dsRNA) mycovirus from this fungus has been fully characterized. The virus genome has five dsRNA segments, ranging in length from 1,180 bp to 2,402 bp. Each dsRNA has a single open reading frame flanked by 5′ and 3′ untranslated regions. The proteins encoded by dsRNAs 1 and 3, an RNA-dependent RNA polymerase (RdRP) and a methyltransferase, respectively, have significant similarity to those of Plasmopara viticola lesion associated polymycovirus 1. The proline-alanine-serine-rich protein encoded by dsRNA 5 is similar to that of Erysiphe necator associated polymycovirus 1. The proteins encoded by dsRNAs 2 and 4 have significant similarity to those of a mycovirus identified in Alternaria sp. FA0703. Phylogenetic analysis based on RdRP sequences showed that this virus clusters with members of the family Polymycoviridae . Based on these observations, this virus, which we have named "Leptosphaeria biglobosa polymycovirus 1", should be classified as a member of the family Polymycoviridae . This is the first report of a polymycovirus in L. biglobosa.

Using high-resolution land cover data to assess structure loss in the 2018 Woolsey Fire in Southern California - Miranda H. Mockrin; Dexter H. Locke; Alexandra D. Syphard; Jarlath O’Neil-Dunne (Journal of Environmental Management, 2023)

Conceptualizing social-ecological drivers of change in urban forest patches - Lea R. Johnson; Michelle L. Johnson; Myla F. J. Aronson; Lindsay K. Campbell; Megan E. Carr; Mysha Clarke; Vincent D’Amico; Lindsay Darling; Tedward Erker; Robert T. Fahey; Kristen L. King; Katherine Lautar; et al. (Urban Ecosystems, 2021)

Assessment of recreational boating as a vector for marine non-indigenous species on the Atlantic coast of Canada - M. Pelletier-Rousseau; R. Bernier; C. Clarke Murray; D. Drolet; A. Lacoursière-Roussel; A. Locke; J. L. Martin; C. H. McKenzie; C. W. McKindsey; T. W. Therriault; N. Simard (Biological Invasions, 2019)

Using multi-locus sequence data for addressing species boundaries in commonly accepted lichen-forming fungal species - Xin Zhao; Samantha Fernández-Brime; Mats Wedin; Marissa Locke; Steven D. Leavitt; H. Thorsten Lumbsch (Organisms Diversity & Evolution, 2017)

Heat waves imposed during early pod development in soybean ( G lycine max ) cause significant yield loss despite a rapid recovery from oxidative stress - Matthew H. Siebers; Craig R. Yendrek; David Drag; Anna M. Locke; Lorena Rios Acosta; Andrew D. B. Leakey; Elizabeth A. Ainsworth; Carl J. Bernacchi; Donald R. Ort (Global Change Biology, 2015)
Heat waves already have a large impact on crops and are predicted to become more intense and more frequent in the future. In this study, heat waves were imposed on soybean using infrared heating technology in a fully open‐air field experiment. Five separate heat waves were applied to field‐grown soybean ( Glycine max ) in central Illinois, three in 2010 and two in 2011. Thirty years of historical weather data from Illinois were analyzed to determine the length and intensity of a regionally realistic heat wave resulting in experimental heat wave treatments during which day and night canopy temperatures were elevated 6 °C above ambient for 3 days. Heat waves were applied during early or late reproductive stages to determine whether and when heat waves had an impact on carbon metabolism and seed yield. By the third day of each heat wave, net photosynthesis ( A ), specific leaf weight ( SLW ), and leaf total nonstructural carbohydrate concentration ( TNC ) were decreased, while leaf oxidative stress was increased. However, A , SLW , TNC , and measures of oxidative stress were no different than the control ca. 12 h after the heat waves ended, indicating rapid physiological recovery from the high‐temperature stress. That end of season seed yield was reduced (~10%) only when heat waves were applied during early pod developmental stages indicates the yield loss had more to do with direct impacts of the heat waves on reproductive process than on photosynthesis. Soybean was unable to mitigate yield loss after heat waves given during late reproductive stages. This study shows that short high‐temperature stress events that reduce photosynthesis and increase oxidative stress resulted in significant losses to soybean production in the Midwest, U.S. The study also suggests that to mitigate heat wave‐induced yield loss, soybean needs improved reproductive and photosynthetic tolerance to high but increasingly common temperatures.